Determination of plate waste in primary school lunches by weighing and visual estimation methods: A validation study - Liz Martins, Margarida (2014)
The aim of this study was to validate the visual estimation method for aggregated plate waste of main dish at Portuguese primary school canteens. For this purpose plate waste at school lunch was measured for 505 individual servings, using weighing individual servings and plate waste and visual estimation method by a 6-point scale, as developed by Comstock et al. (1981). A high variability of initial serving weights was found with serving sizes ranging from 88.9 to 283.3 g and with a coefficient of variation ranging from 5.5% to 24.7%. Mean plate waste was 27.5% according to the weighing method. There was a significant bias in the conversion of the visual waste estimations to actual waste, being overestimated by an average of 8.0 g (ranging from -12.9 g to 41.4 g). According to Bland and Altman plot, the mean difference between methods was of 8.0 g and the amplitude interval was 102.6 g. The study showed that the visual estimation method is not as accurate as the weighing method in assessing nonselective aggregated plate waste at primary school canteens. Our findings are thus very important on considering plate waste assessment, since the wide variation on initial servings introduces a relevant bias when considering standard portions or a random sample of initial servings. Although, greater convenience, time-saving and the possibility to monitor plate waste of large groups, make the visual estimation method an important method to assess plate waste at school canteens, these results highlighted the need of portions standardization and control of initial servings to allow for its use.